Determinasi Emosional Merek Dan Kepercayaan Merek Terhadap Kepuasan Pelanggan Pada Skin Care Clinic - rahmawati, selvi; Ramdan, Asep M.; Komariah, Kokom (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.05.TAHUN 2019DO - 10.24843/EEB.2019.v08.i05.p03, 2019)
The purpose of this study was to determine the emotional determination of brands and brand trust in customer satisfaction at skin care clinic. The research method used by the authors in this study is to use the sampling method included in the sample random sampling, by distributing questionnaires as much as 290 respondents to skin care clinic customers. The analysis technique used by the writer is to use multiple linear regression analysis techniques, multiple correlation coefficient and determination coefficient. And to test the hypothesis the author uses a statistical test partially (t test) and simultaneous test (f test). The results of the test coefficient of determination seen from the value (Adjusted R²) of 0.603 means that the influence of Emotional Brands and Brand Trust on Customer Satisfaction is 60.3% The remaining 39.7% is influenced by other factors not explained in this study. And based on the multiple correlation coefficient test seen from the R value of 0.606 shows that there is a very strong relationship between Emotional Brands and Brand Trust with Customer Satisfaction. Based on the f test the probability value sig. 0.00 <0.05 which means that together Emotional Brands (X 1 )  and Brand Trust (X 2 )  have a significant effect on Customer Satisfaction (Y). Based on the t test shows that Emotional Brands (X 1 )  have a significant effect on Customer Satisfaction (Y), Brand Trust (X 2 )  has a significant effect on Customer Satisfaction (Y). Keyword : Emotional Brands, Brand Trust, Customer Satisfaction.